PEMBERDAYAAN EKONOMI KARYAWAN PESANTREN OLEH KOPERASI AL-MAWADDAH STUDI KASUS PESANTREN PUTRI AL-MAWADDAH - Danty Safira Dewi; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The research goal is to figure out the role of the Al-Mawaddah Islamic Girl Boarding School or Kiswah against economic empowerment employee of boarding school. The research method used is descriptive qualitative approach with case studies. Data collected by interviews and observations directly to the informant that is in charge of the cooperative and the community surrounding the village of Coper Jetis Ponorogo and secondary data collection is derived from the journal, text books and other literature.Results from this study is a Kiswah role in the economic empowerment of the employees but still less perfect or less than optimal. The employees economic empowerment conducted by the Cooperative Al-Mawaddah Islamic Girl Boarding School or Kiswah by making Kiswah as employment and to increase their income. Going forward, Kiswah will change the shape of this cooperative that previously was business cooperatives into credit unions or other forms of cooperatives.